2020
DOI: 10.1080/20477724.2020.1719325
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and genotypic characterisation of Streptococcus pneumoniae isolated from children in Malaysia

Abstract: Streptococcus pneumoniae (S. pneumoniae) is one of the main causative agents of pneumococcal diseases. To date, more than 90 distinct serotypes have been identified. Implementation of vaccines has caused a drastic reduction in vaccine-serotype pneumococcal diseases but increase in cases due to non-vaccine serotype has been observed in Malaysia. However, further investigation on different serotype incidence in Malaysia is needed and the rate of pneumococcal vaccination for new-born babies in Malaysia remains lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…The results showed 16 and 42 amino acid substitutions in the STMK conserved motif of PBP1a (Thr 371 → Ala) and PBP2x (Thr 338 → Ala), respectively. Moreover, we found no substitution in the three conserved motifs of PBP2b , being in agreement with the results of Talebi et al 28 and in contrast with the results reported by Ling Goh et al 29 . In addition, the findings indicate that 20.7% of the PNSP isolates reveal no alterations in three conserved motifs of PBPs.…”
Section: Discussionsupporting
confidence: 93%
“…The results showed 16 and 42 amino acid substitutions in the STMK conserved motif of PBP1a (Thr 371 → Ala) and PBP2x (Thr 338 → Ala), respectively. Moreover, we found no substitution in the three conserved motifs of PBP2b , being in agreement with the results of Talebi et al 28 and in contrast with the results reported by Ling Goh et al 29 . In addition, the findings indicate that 20.7% of the PNSP isolates reveal no alterations in three conserved motifs of PBPs.…”
Section: Discussionsupporting
confidence: 93%
“…Whilst our study found 33.3% of carried S. pneumoniae serotypes to be PCV13 VT and 14.3% PCV10 VT, studies from Peninsula Malaysia showed a higher proportion of S. pneumoniae VT carriage, with up to 69.5% being PCV13 VT and 40.6% being PCV10 and PCV7 VT [34,35]. Certainly, VT S. pneumoniae cause the majority of pneumococcal disease in Peninsular Malaysia with 66.3% of RTI in children being caused by PCV13 VT and 60% by PCV10 VT [36]. As PCV13 serotypes 1, 6B, 14, 19F, 19A are commonly associated with disease in Malaysia [10,37], the carriage of 6B and 14 (which was in children) here is of interest for public health, particularly as these serotypes are included in both PCV10 and PCV13.…”
Section: Discussionmentioning
confidence: 98%
“…AMR is an increasing issue across Asia; multidrug resistant S. pneumoniae and K. pneumoniae are of particular concern [17,36,39,40]. In Malaysia, antibiotics are commonly prescribed for the treatment of URT infections, although inappropriate antibiotic choice and dosage have been shown in up to 40% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…We observed the most frequent mutations at Thr-371-Ala/Ser (STMK motif) and Pro-432-Thr (adjacent to SRN motif) in PBP1a, corresponding to the common mutation sites in penicillin non-susceptible S. pneumoniae [22,23]. The block mutation identified at amino acid positions 574-577 in PBP1a has been previously associated with intermediate-to high-level penicillin resistance [24,25].…”
Section: Discussionmentioning
confidence: 63%
“…pneumoniae and H. influenzae strains with non-susceptible phenotypes for ampicillin were examined for potential amino acid substitution in the genes encoding for penicillinbinding proteins (pbp1a, pbp2b, and pbp2x in S. pneumoniae and ftsI, also known as pbp3, in H. influenzae). The primer sequences and PCR conditions for the amplification of pbp and ftsI genes were adapted from published studies [12,22,63]. The PCR products were then purified using MEGAquick-spin™ Plus Total Fragment DNA Purification Kit (iNtRON Biotechnology, South Korea), and sent for sequencing by a commercial sequencing service provider (First BASE Laboratories, Malaysia).…”
Section: Molecular Detection Of Penicillin Resistance-conferring Genesmentioning
confidence: 99%